Article Review: Personal Hygiene sebagai Faktor Risiko Infeksi Protozoa Usus pada Anak Sekolah - Luthfi Shiba Andana; Suryadi Islami; Betta Kurniawan; Jhons Fatriyadi Suwandi (CV. Jasa Sukses Abadi, 2026)
Intestinal protozoa infections remain a significant public health problem, particularly among school children in developing countries such as Indonesia. These infections contribute substantially to morbidity related to gastrointestinal disorders, including both acute and chronic diarrhea. Transmission of intestinal protozoa generally occurs through the fecal–oral route and is strongly influenced by personal hygiene practices in daily life. This article aims to determine the association between personal hygiene and the risk of intestinal protozoa infections among elementary school children through a literature review method. A literature search was conducted in the PubMed and Google Scholar databases using the keywords personal hygiene, intestinal protozoa infections, and school children, covering publications from 2011 to 2025. Relevant articles were selected and critically analyzed to identify the relationship between personal hygiene and the incidence of intestinal protozoa infections. The findings indicate that poor personal hygiene, particularly the habit of not washing hands with soap before meals and after defecation, inadequate nail hygiene, nail biting, and poor food and beverage hygiene, is significantly associated with an increased risk of intestinal protozoa infections. Several studies also reported a statistically significant higher risk of infection among children with poor personal hygiene compared to those with good hygiene practices. In conclusion, personal hygiene is a significant risk factor for intestinal protozoa infections.